VIII Premi Internacional Dibuix Joan Miro. - Palau de la Virreina, Barcelona; Borràs, Maria Lluisa; Comi, Ricky; Cruanas, Lluis Bosch i; Puig, Arnau; Teixidor, Joan (Barcelona : Premi Internacional Dibuix Joan Miró, 1969)
Yoshida, Masaji ; Moreno, Servando Cabrera ; Lison, Miguel Garcia ; Pietra, Ugo La ; Rusek, Jaroslav ; Vidal, Eugènia ; etc.
Spaans
VIII Premi Internacional Dibuix Joan Miró, Palau de la Virreina, Barcelona, 11 de juny al 11 de juliol, 1969
kunstcatalogus